CEOs' strategic orientations in the most successful Slovenian companies - Berginc, Dario (Management, 2014)
This article presents the concept of a CEOs' strategic orientation as one of the most important elements of the research into a company's successfulness. Managerial perception is in many ways more important than environmental analysis, since ceos determine their company's future strategic orientations. A study of CEOs' strategic orientations can provide better information regarding companies' strategic orientations. We performed a qualitative study of CEOs from a sample of the most successful Slovenian companies. The research results indicate numerous commonalities between CEOs opinions and standpoints, as well as some differences in relation to the characteristics of the companies and industries in which they operate.
Keywords: managerji; podjetja; poslovna strategija; poslovna uspešnost; razvojna strategija; Slovenia; Slovenija